How do I vote the scoundrels out?: why voters might not punish corrupt politicians at the polls - Johnston, Michael (Crime, law and social change, 2013)
While we frequently hope electoral democracy can serve as an important constraint on corruption, there are good reasons to think that such might not be the case. This paper analyzes two closely-related questions: should we expect voters to punish corrupt politicians or parties at the polls, and should we expect such influences to check corruption generally? While there have been clear-cut cases in which such punishments have been massive and decisive, they are much the exception. Indeed, a variety of factors having to do with corruption as a concept and as a political issue, the nature of competitive electoral politics, and more recent economic and political trends reshaping important aspects of liberal democracy, all point toward a pessimistic assessment. Ideas for changing that state of affairs are few, because the difficulties reside less at the level of fixable "problems" and more with the inherent workings of liberal political and economic systems. Efforts to improve the quality of news coverage and civic education, however, and any prospects for strengthening and deepening civil society, may hold out some hope for the longer term.